The effect of political risk on China's foreign direct investment - Fidelis Ayangbah; Bismark Addai; Adjei Gyamfi Gyimah (Cogent Economics & Finance, 2022)
This study examines the impact of political risk on Chinese outward foreign direct investment (OFDI) and what motivates their preferred location. The study also analyzes the OFDI of other countries to enhance the comparison of China and other countries' OFDI sensitivity to political risk. The study used annual panel data on 134 countries from 2003 to 2017. The results indicate that China's OFDI tends to favor countries and regions with higher expropriation risk, and China's OFDI exhibits strong resource-seeking motives and weak market-seeking motives. On the other hand, OFDI in countries around the world tends to favor countries and regions with lower expropriation risk and conflict risk, and OFDI in those countries exhibits market-seeking motives. The study results also show that China's political risk preference and investment motives depend on the level of economic development and the presence of natural resources in the host country.
Keywords: D7; F2; F3; F4; 330; foreign direct investment; expropriation risk; outward foreign direct investment; political risk